A state-of-the-art comprehensive review summarizing the emerging data on endoscopic ultrasound-guided liver diseases management. Issue 12 (December 2021) - Sbeit, Wisam; Kadah, Anas; Mahamid, Mahmud; Mari, Amir; Khoury, Tawfik
Abstract : Liver diseases are among the most common diseases worldwide accounting for substantial morbidity and mortality. Most liver diseases necessitate radiological evaluation or accurate diagnosis and recently for management as well. In the last decade, the application of therapeutic endoscopic ultrasound (EUS) procedure has been increasingly utilized for the management of various liver diseases. In this comprehensive narrative review article, we provide systematic overview on EUS-guided therapeutic interventions in various liver diseases summarizing most updated data regarding technical success, outcomes and safety profiles. Overall, 35 articles have reported on the use of EUS in the treatment of liver diseases with excellent technical success, favorable radiological response and high safety profiles for EUS-guided treatment of solid and cystic liver lesion and for EUS-guided angiotherapy for gastric varices, except for EUS-guided cyanoacrylate glue injection which was associated with life-threatening fatal systemic embolization adverse events. This suggests that EUS-guided intervention is a new promising therapeutic intervention for the treatment of various liver diseases with durable effect and a limited potential for adverse events.